Disaster characteristics and policy implications of the MS6.2 Jishishan earthquake in Gansu Province - Xu Wang; Benyong Wei; Yanjun Wen; Jiakang Wang; Wenhua Qi; Donghui Chen (地震科学进展, 2025)
On December 18, 2023, a magnitude 6.2 earthquake struck Jishishan County, located in the Linxia Hui Autonomous Prefecture of Gansu Province, resulting in significant casualties, building collapses, and various geological hazards. This study examines the disaster characteristics of the Jishishan earthquake by analyzing its spatiotemporal context within the historical seismicity of Gansu Province and comparing it to other earthquakes of similar magnitude in the region. Using data collected from field investigations, the study further explores the contributing factors to the disasters from multiple perspectives, including geological, structural, and socio-environmental aspects. The results indicate that the Jishishan earthquake affected area is seismically active and currently undergoing a relatively high level of regional seismicity. Compared with past earthquakes of similar magnitudes, the Jishishan event resulted in significantly greater disaster losses. The primary factors contributing to the earthquake’s high destructiveness include a thrust-type seismogenic structure, a shallow focal depth, and site amplification effects due to thick loess deposits. Additionally, widespread use of civil or brick-wood buildings with poor seismic resistance was a major cause of the severe structural damage and building collapses observed in the disaster zone. The earthquake occurred in the early hours of the night, when people were sleeping, which greatly shortened the emergency evacuation and response time, aggravating casualties. Harsh environmental conditions such as low temperatures, high-altitude plateaus, and steep terrain-not only reduce the survival chances of individuals trapped under debris but also significantly shorten the golden window for rescue and increase operational difficulty of responders. The high proportion of vulnerable populations, including the elderly and children, compounded by their limited disaster awareness and weak emergency response capabilities, further exacerbated regional casualties. Based on these findings, this study offers targeted recommendations for improving earthquake disaster prevention, mitigation, and emergency response in the region.